Plasma phospho‐tau in familial Alzheimer's disease: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - O'Connor, Antoinette; Karikari, Thomas K.; Poole, Teresa; Khatun, Ayesha; Swift, Imogen; Heslegrave, Amanda J.; Abel, Emily; Chung, Elisha; Weston, Philip S.J.; Polke, James; Pavisic, Ivanna M.; Rossor, Martin N.; et al.
Abstract: Background: Blood biomarkers have the potential to advance clinical care and accelerate the development of disease‐modifying treatments. P‐tau181 is a promising blood biomarker, with levels increasing in Alzheimer's disease (AD) dementia (doi:10.1016/j.jalz.2018.02.013). However, a better understanding of the timing and trajectory of plasma p‐tau181 changes is needed. Therefore, we conducted a longitudinal study in familial AD (FAD). Methods: Using an in house Single molecule array method, P‐tau181 was measured in 153 plasma samples from 70 individuals from families with PSEN1 or APP mutations (mean ± SD = 2.2 ±1.3 samples/participant;median [IQR] duration of follow up =1.0 (0, 3.7) years). We compared plasma p‐tau181 between symptomatic mutation carriers, presymptomatic carriers, and noncarriers, adjusting for age and sex. We also examined the relationship between plasma p‐tau181 and estimated years to/from symptom onset (EYO), as well as years to/from actual symptom onset (AAO) in a symptomatic subgroup. In addition, we studied associations between plasma p‐tau181 and clinical severity, as well testing for differences in concentration between genetic subgroups (PSEN1 vs APP carriers, PSEN1 pre‐codon 200 vs PSEN1 post‐codon 200 carriers). Results: 24 of the asymptomatic participants were mutation carriers (mean baseline EYO ‐9.6 years); 27 were noncarriers. Compared with noncarriers, plasma p‐tau181 concentration was higher in symptomatic (p<0.001) and presymptomatic mutation carriers (p<0.001) (Figure 1). Plasma p‐tau181 discriminated symptomatic (AUC 0·93[95% CI 0·84−0·98]) and presymptomatic (AUC 0.86 [95% CI 0·73−0·95]) carriers from noncarriers. Plasma p‐tau181 concentration increased in mutation carriers from 16 years prior to estimated symptom onset (p=0.049) (Figure 2). Plasma p‐tau181 in symptomatic mutation carriers, modelled using AAO, appeared eventually to plateau. Longitudinal p‐tau181 measures demonstrated significant inter‐ and intra‐individual variability, with some participants exhibiting large changes over relatively short time intervals. We did not find a difference in plasma p‐tau181 concentration between APP and PSEN1 carriers, but there was weak evidence (p=0.053) that symptomatic PSEN1 post‐codon 200 carriers had a 54% higher p‐tau181 concentration (95% CI:1% lower, 138% higher) than pre‐codon 200 carriers. Conclusion: Our finding that plasma p‐tau181 concentration is increased in presymptomatic and symptomatic FAD suggests its potential utility as an easily accessible biomarker of AD pathology.